2010
DOI: 10.1590/s2176-94512010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação clínica e polissonográfica do aparelho BRD no tratamento da Síndrome da Apneia Obstrutiva do Sono

Abstract: OBJETIVOS: este trabalho de pesquisa teve o intuito de realizar uma avaliação clínica e polissonográfica do efeito de um aparelho intraoral (AIO) para tratamento da Síndrome da Apneia Obstrutiva do Sono (SAOS), desenvolvido e testado por duas universidades federais brasileiras. MÉTODOS: a amostra constou de 50 pacientes (idades entre 18 e 65 anos, sendo 33 homens e 17 mulheres) com diagnóstico polissonográfico inicial de SAOS de grau leve e moderado. Todos os pacientes submeteram-se a uma nova avaliação poliss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Our results were in agreement with the findings of other studies that showed a high prevalence of the disease in the 4 th and 5 th decades of life 3,12 and that men as strong candidates to have apnea 3,27 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results were in agreement with the findings of other studies that showed a high prevalence of the disease in the 4 th and 5 th decades of life 3,12 and that men as strong candidates to have apnea 3,27 .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with their findings, the mean neck circunference in patients with AHI bellow 5 was 35.4 cm and in patients with AHI over 5, the mean values were over 40 cm. All values of vertical facial measurements in this study were higher in the group with AHI over 5, indicating that a long face may contribute to the narrowing of the upper airways space 7,11,12,24,30 . Our predictive model for AHI over 5 indicated that the larger the measures of Tr-Gla, Sn-Me and N.C., the greater would be the likelihood of having OSA.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Data collection took place through the sample of patients at risk for OSA who underwent polysomnography. This population was divided into groups according to the AHI: Normal (≤ 5 events/hour), Mild (5-14 events/hour), Moderate (15-29 events/ hour), and Severe (≥ 30 events/hour), which will serve as a basis for correlations with secondary data [7,8].…”
Section: Data Collectionmentioning
confidence: 99%
“…AHI is calculated by dividing the total number of apneas and hypopneas by the number of hours of sleep. AHI is considered normal when less than 5 events per hour occur, mild OSA between 5 and 14 events/hour, moderate OSA between 15 and 29 events/hour, and severe OSA ≥ 30 events/hour [7,8].…”
Section: Rbfex Introductionmentioning
confidence: 99%